Genesis of sociological periodical in Serbia - Trkulja, Jovica D (Sociološki pregled, 2018)
The first sociological journals in Serbia appeared in 1920, Društveni život (Social life), and in 1938 Sociološki pregled (Sociological review). The key role in initiation and publication of these journals have had professors of faculties of law in Belgrade and Subotica, led by professors Mirko M. Kosić and Đorđe Tasić. In addition to these journals important role in this area had also “Biblioteka javnog prava” (Series on the Public Law), series “Politika i društvo” (Politics and Society) and a paper Napred (Forward), edited by professor Mihailo Ilić. These professors, together with their colleagues from Belgrade’s Faculty of Law, have given a substantial contribution to the development of sociological periodicals in Serbia. By acting in this way they have invested a substantial effort in establishing sociology in Serbia, on the theoretical heritage of French and, to a significantly smaller extent, German sociology.These sociological journals and series would cease to be published after a few years due to lack of financial resources, war, and post-war rigid rule of the Communist party manifested in lack of support for science and periodical publications. Now liberated country saw a dark period for all social sciences. This situation had specifically affected sociology and sociological periodical which had practically vanished. Despite that, the heritage left by Kosić, Tasić and Ilić and their associates (with two professional sociological journals, two acclaimed book series, and one progressive paper) have been useful in the sixties of XX century to their successors at the University of Belgrade as a solid foundation for constituting sociology as a scientific and academic discipline in Serbia.
Keywords: paper Napred; book series “Politika i društvo”; “Biblioteka javnog prava”; journals Društveni život and Sociološki pregled/ Sociological Review; Mihailo Ilić; Đorđe Tasić; Mirko M. Kostić; Serbian periodical